2018
DOI: 10.1007/s11136-018-1885-5
|View full text |Cite|
|
Sign up to set email alerts
|

Health-related quality of life in coronary heart disease: a systematic review and meta-analysis mapped against the International Classification of Functioning, Disability and Health

Abstract: The ICF provides a framework for evaluating and understanding the impact of CHD on HRQoL. The results demonstrate that HRQoL goes beyond physical symptoms, with activity limitations, social support and participation, and personal perceptions identified as key ICF domains in CHD assessment. Further investigations are needed to unravel the dynamic and inter-relationships between these domains, including longitudinal trends in HRQoL indicators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 51 publications
1
26
0
1
Order By: Relevance
“…Coronary artery disease (CAD) is one of the leading causes of death in developed countries, and it is associated with deteriorated quality of life, disability, and premature death [1]. The usual surgical treatment involves coronary artery bypass graft surgery (CABG).…”
Section: Introductionmentioning
confidence: 99%
“…Coronary artery disease (CAD) is one of the leading causes of death in developed countries, and it is associated with deteriorated quality of life, disability, and premature death [1]. The usual surgical treatment involves coronary artery bypass graft surgery (CABG).…”
Section: Introductionmentioning
confidence: 99%
“…In connection with the effects of pain that are felt to be subjective, this can lead to psychological limitations such as anxiety arising from the sudden onset of illness and a fear of sudden death (Beltrame, 2017). Due to the feeling of pain, the physical restrictions, social disability, anxiety and depression, CAD patients are very vulnerable to a decline in health status (De Smedt et al, 2015;Le, Dorstyn, Mpfou, Prior, & Tully, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The QoL of YAC patients seemed low and lower than that of the healthy population (Schweikert et al, 2009;Wong et al, 2013;Leung Yinko et al, 2014). A recent systematic review and meta-analysis showed that this was also true for older adult patients (mean age = 61 years old) with coronary heart disease (Le et al, 2018). This may not be the case for younger congenital heart disease patients (7-17 years old) who had QoL levels identical to those of healthy controls (Reiner et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Studies that include young adults coping with a cardiac illness are scarce (McDonough, 2009 ; Wong et al, 2017 ). Systematic reviews interested in the psychosocial aspects of individuals coping with a cardiac illness do not specifically deal with young adults (Fredericks et al, 2012 ; Foxwell et al, 2013 ; Herr et al, 2014 ; Doyle et al, 2015 ; Li et al, 2015 ; Tully et al, 2015 ; Ooi et al, 2016 ; Le et al, 2018 ), and studies that do usually focus on patients coping with congenital heart diseases (Van Rijen et al, 2004 , 2005a , b ; Fredriksen et al, 2009 ; Asp et al, 2015 ; Uzark et al, 2015 , 2016 ; Jackson et al, 2017 ; Abda et al, 2018 ; Andonian et al, 2018 ; Grady et al, 2018 ; Monti et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%